Aktivitas Antiinflamasi Ekstrak Etanol Daun Karas (Aquilaria malaccensis Lamk.) - Apridamayanti, Pratiwi; Sanera, Ferlino; Robiyanto, Robiyanto (Pharmaceutical Sciences and Research, 2018)
Karas (Aquilaria malaccensis Lamk.) leaves contain secondary metabolite such as alkaloid, flavonoid, phenol, antraquinone, and triterpenoid. Flavonoid compound has anti inflammatory activity. This research was conducted to investigate the effective anti inflammatory dose from the reduction of rat paw edema using plethismometer. Karas leaves was macerated with 96% ethanol and then evaporated until crude extract was obtained. This research was carried out using 25 male rats that was divided into 5 treatment groups, negative control (CMC-Na 1%), positive control (Natrium diclofenac 4.5 mg/kgBW), dosage I (45 mg/kgBW), dosage II (90 mg/kgBW), and dosage III (180 mg/kgBW). The extract was administrated orally half an hour before the induction of 0.1 ml carragenan 2% solution. The anti inflammatory activity was observed from the volume of edema, AUC, and the percentage of antiinflammatory activity. The data was analyzed by ANOVA using SPSS. The result shows that there was a significant difference between negative control with the treatment groups (dosage I, II, and III). There was no significant difference between positive control with dosage II and III, however there was a significant difference to dosage I. The percentage of antiinflammatory activity of positive control, dosage I, dosage II, and dosage III was 39.3%, 22.9%, 29.6%, and 37.9% respectively. The conclusion of this research was that the effective dose of ethanolic extract form karas leaves was 180 mg/kgBB.